Who Speaks for Water in Times of Crisis? A Case for Co-production of Engineering and Governance - Nabavi, Ehsan (Frontiers in Communication, 2022)
Studying the relationship between water expertise and the state’s governance is important as it helps to explain the mechanism by which a certain group of experts rise to power, speaking for water—its challenges, and opportunities. This is particularly of concern in the times of crisis when the society does not know where to turn, and who to trust. Some aspects of this relationship have been addressed in the literature through now-familiar notions such as hydraulic bureaucracy and the hydraulic mission, in which the prevailing role of engineers in problem framing and communicating solutions has been brought into the spotlight. However, the reciprocal nature of this relationship, particularly in difficult times when the society is fraught with fear of an uncertain future, has remained heavily under‐researched. This paper aims to fill that gap by introducing the concepts of ‘engineering epistemic community’ and the ‘co-production of engineering and governance’. Through using Iran’s looming water crisis, the paper demonstrates the analytic potential of the proposed concepts. Iranian case shows how engineering and governance co-produce one another through an ongoing process of mutual constitution. On one hand, engineering artifacts are integral part of state-making process; while on the other hand, engineers become the gatekeepers of knowledge-making processes. This creates a hegemonic power for engineers, their epistemic practices, and institutions of power. This research also illustrates how this co-production reinforces the epistemic injustice in water governance by marginalizing non-engineering communities most particularly indigenous knowledge-holders. This is, of course, a great concern as it can lead to depoliticization of the water crisis, monopolization of water science, and demonization of participation in water governance.